2018
DOI: 10.2478/jtes-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Contradictions in Higher Education

Abstract: The present paper is a literature and experience summary about contradictions existing in higher education, nowadays. Thus, it is important to understand the underlying reasons and historical background to find ability to move towards higher education system for sustainability. Seven main contradiction groups have been distinguished and an overview is given in the article. The analysis is more focused on a situation in Latvia and the post-soviet space since the authors are well acquainted with the system. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
6
1
1
Order By: Relevance
“…There some students were confusedly not informed or even did not know exactly what had happened at the university or as new students they should have been aware of the whole process. In fact, this result is a bit different from the research by Laura DzelzkalÁja and Jnis Kapenieks [20] in which socialization is mostly, if not 100 per cent, attended by new students, as it was like a game plan for them to follow the whole process during the years of study. The research also states that it is essential to have a clear interactive university structural framework that put into action the university mission and vision and restrain any cultural and political effects on the implementation of technological strategies…”
Section: Socialization Of Academic Processcontrasting
confidence: 81%
“…There some students were confusedly not informed or even did not know exactly what had happened at the university or as new students they should have been aware of the whole process. In fact, this result is a bit different from the research by Laura DzelzkalÁja and Jnis Kapenieks [20] in which socialization is mostly, if not 100 per cent, attended by new students, as it was like a game plan for them to follow the whole process during the years of study. The research also states that it is essential to have a clear interactive university structural framework that put into action the university mission and vision and restrain any cultural and political effects on the implementation of technological strategies…”
Section: Socialization Of Academic Processcontrasting
confidence: 81%
“…The changes happening in society has a big affect on education (Mohammadi & Moradi, 2017). The global change in the field of education caused by the tremendous change in technology, globalization, and human mobility has changed the expectation in the educational system (Dzelzkaleja & Kapenieks, 2018). This was confirmed by Van Hong, Tuyen, & Luong, (2018) who revealed that 21st-century teachers and lecturers were required to have at least three competencies, one of which was the ability to apply technology in learning.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, as faculty at higher education institutions are scholars, they have the need to teach and research at the same time so as to publish and get promoted and tenured (Quimbo & Sulabo, 2014). The knowledge provided at academic institutes by these scholars is useful to be applied in practice if knowledge management is maintained in higher education institutions (Dhamdhere, 2015).…”
Section: The Development Of Lecturers In Higher Education Institutions In Vietnammentioning
confidence: 99%